The Impact of Implementing Merdeka Belajar Curriculum by Utilizing Digital Media on Changes in Knowledge, Attitudes and Skills of Madrasah Ibtidaiyah Al I'anah Students, Duren Village, Klari District, Karawang Regency - Siti Masruroh; Hoerudin Hoerudin; Bayu Priyatna (Unib Press, 2023)
Merdeka Belajar Curriculum is a curriculum of a set of plans and arrangements regarding the objectives, content and learning materials of the methods used as guidelines for organizing learning activities to achieve certain educational goals. The central government establishes a basic framework and curriculum structure which serves as a reference for the development of the operational curriculum for education units. According to the National Standards Agency, Merdeka Belajar is education so that students can choose subjects of interest. This is done so that students can optimize their talents. The purpose of this writing, namely to find out the impact of the implementation of the independent learning curriculum on the attitudes, knowledge and skills of Madrasah Ibtidaiyah Al'Ianah students in Duren Village, Klari Distric. Implementation method with observation and field studies.